Actuator fault accommodation strategy for a team of multi-agent systems subject to switching topology. (December 2015) - Saboori, Iman; Khorasani, Khashayar
Abstract: A cooperative actuator fault accommodation strategy for a team of linear time-invariant (LTI) multi-agent systems with a switching topology and directed communication network graph is studied in this paper. The faults can simultaneously occur in more than one agent. The proposed fault accommodation strategy is based on a consensus algorithm that weights the effort that each agent contributes to the consensus achievement of the team. The stability property of the proposed weighted consensus algorithm is investigated based on Lyapunov analysis. Moreover, a fault index is introduced to quantitatively measure the effects of inaccuracy in estimation of fault severities on consensus performance of the multi-agent team. This index is exploited to reconfigure the agents weights in such a manner that healthier agents contribute more control efforts to compensate for the faulty agents controller degradations. Both actuator loss-of-effectiveness and actuator saturation faults are investigated and the capabilities and effectiveness of our proposed approach is shown by numerical simulations and comparisons with centralized and decentralized fault recovery approaches that are available in the literature.